=>
=>
=>
=>
=>
=> or
ok i know this is easy just forgot a few rules along the way the expression is
1 + 1 = 2
2 - t 2+t
how would i go about this i thought you make it into 2 equations that = 2 ie.
1 =2 , 1 = 2 then solve for t in both but i came up with 3 and -3
2-t 2+t
when i checked my work they did not equat 2 but -2
please help
thank you
i was working. went to a trade school for audio engineering and met my wife whom is finnish and moved to finland. been living here since 2006 just now realized how good it is that the colleges in finland are FREEE so decided to better my life and take advantage of the free schooling